PERANCANGAN DAN PENGEMBANGAN APLIKASI JAM PENGINGAT WAKTU SHOLAT ARAH KIBLAT DAN REKOEMNDASI MASJID TERDEKAT - Yuda Putra Utama; Elfi Tasrif; Yeka Hendriyani (Universitas Negeri Padang, 2016)
People nowdays have a high mobility that make some of obligation had been forgotten.the most important obligation for muslim is praying five times a day limited information about praying time sometime make the obligation had been neglected or even forgotten.usually when the condition is for far from mosque and/or in a trip.the information of qibla is needed for avoid this problem,especially in places or areas are far from mosque. This application is a mobile application technology based Location Based Service (LBS) that is built on the Android platform, using Android Studio IDE and Google APIs in its development. In determining the time of prayers used two methods, by determining the time the degree of the sun and using a formula that is expressed with the time / clock, in determining the direction of the Qibla used two methods with the formula triangles ball and the position of the sun and the method of application also utilizes the Global Positioning System (GPS) which are applied with the help of Google Map. This application is able to display Qibla direction and prayer schedules wherever the location of the nearest mosque user is located. Users can download the prayer schedule and location-based Qibla direction and displays the nearest mosque on user location is equipped with navigation features to reach the mosque by using the Google Map. Keywords: Android Applications , Mosque , Prayer Times , Qibla Direction , GPS , Google Map